Implementing CIFS: The Common Internet File System - Hertel, Christopher (Bruce Perens' open sources series., 2003)
"The book that Microsoft should have written, but didn't." -Jeremy Allison, Samba Team "Your detailed explanations are clear and backed-up with source code-and the numerous bits of humor make a dry subject very enjoyable to read." -J.D. Lindemann, network engineer, Adaptec, Incorporated The first developer's guide to Microsoft®'s Internet/Intranet file sharing standard For years, developers and administrators have struggled to understand CIFS, Microsoft's poorly documented standard for Internet file sharing. Finally, there is an authoritative, cross-platform guide to CIFS capabilities and behavior. Implementing CIFS not only delivers the priceless knowledge of a Samba Team member dedicated to investigating the inner workings of CIFS, it also identifies and describes crucial specifications and supporting documents. Provides essential information for designing and debugging large Windows® and/or Samba networks Offers clear, in-depth introductions to Server Message Block (SMB), NetBIOS over TCP/IP (NBT), browser services, and authentication Drills down into the internals of CIFS, exposing its behavior on the wire and at the desktop-and its strange quirks Presents illustrative code examples throughout Reflects years of work reviewing obscure documentation, packet traces, and sourcecode Includes the SNIA CIFS Technical Reference Implementing CIFS will be indispensable to every developer who wants to provide CIFS compatibility-and every administrator or security specialist who needs an in-depth understanding of how it really works.